Corporate Responsibility for Consumer Losses in Tte Digital Economy Era - Anindya Bidasari; Dyra S Madhona; Sri Murni; Mieke Anggraeni Dewi; Darmawan Tri Budi Utomo (Universitas Muhammadiyah Palu, 2025)
The development of the digital economy has created a major transformation in the patterns of interaction between businesses and consumers across various sectors, ranging from e-commerce and digital financial services to data-driven platforms. While this transformation provides convenience and efficiency in economic activities, it also presents serious challenges regarding legal protection for consumers. Issues such as data breaches, online fraud, and algorithmic manipulation have emerged as tangible risks resulting from the imbalance of power between digital corporations and users. This article aims to examine the legal responsibility of corporations in the context of the digital economy by employing a normative juridical approach through an analysis of relevant legislation, legal responsibility principles, and case studies on consumer rights violations in online environments. The findings indicate that although Indonesia has several legal instruments such as the Consumer Protection Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law, their implementation still faces significant obstacles in law enforcement and inter-agency coordination. The complexity of cross-border jurisdiction and the weakness of online dispute resolution mechanisms further complicate corporate accountability. Therefore, strengthening regulations, establishing independent supervisory institutions, and increasing consumer legal awareness are necessary to create a balance between technological innovation and the protection of public rights in the rapidly evolving digital economy.